Effect of active packaging atmosphere on the shelf life of chilled stored steaks of barracuda Sphyraena jello - Remya, S.; Mohan, C. O.; Ravishankar, C. N.; Sivraman, G. K.; Jha, A. K.; Venkateshwarlu, G. (Indian Journal of Fisheries, 2018)
In the present study, effect of an active reduced oxygen packaging atmosphere on the shelf life of barracuda (Sphyraena jello) fish steaks stored at 0-2oC was analysed. Barracuda steaks of 2.5 cm were divided into two batches; the first batch served as control, which was aerobically packed (AP) inside a multilayer film pouch of ethylene-vinyl alcohol (EVOH) with high barrier properties and the second batch packed in EVOH pouch was attached with a commercial oxygen (O2) scavenger (OS). OS reduced the amount of O2 inside the package to less than 0.01% within 24 h. On 12th day of storage, there was a 2 log difference in the total mesophilic count of steaks in OS attached pouches, compared to control. The 2 mg malonaldehyde kg-1 limit of thiobarbituric acid (TBA) value, which is an index of secondary lipid oxidation, was exceeded in control, on 12th day of chilled storage. Based on the sensory score, control was rejected on 12th day, while OS steaks were acceptable till 20th day. The results indicate that OS is efficient in enhancing the storage life of fish by limiting the oxygen present inside the package.